Effect of different light sources on degree of conversion, hardness and plasticization of a composite - Barreto, Bruno de Castro Ferreira; Catelan, Anderson; Okida, Ricardo Coelho [UNESP]; Gonçalves, Gisele Fernanda [UNESP]; Silva, Gisele Rodrigues; Santos, Paulo Henrique [UNESP]; Xavier, Tathy Aparecida; Aguiar, Flávio Henrique Baggio; Soares, Carlos José (My University, 2013)
Clinical performance of composite resins depends largely on their mechanical properties,and those are influenced by several factors,such as the light-curing mode. The purpose of this study was to evaluate the influence of different light sources on degree of conversion(DC), Knoop hardness(KHN) and plasticization(P) of a composite resin. Disc-shaped specimens (5 x 2 mm) of Esthet-X(Dentsply) methacrylate-based microhybrid composite were light-cured using quartz-tungsten-halogen (QTH) Optilight Plus(Gnatus) or light-emitting diode(LED) Ultraled(Dabi Atlante) curing units at 400 and 340 mW/cm2 of irradiance, respectively. After 24 h, absorption spectra of composite were obtained using Nexus 670(Nicolet)FT-IR spectrometer in order to calculate the DC.The KHN was measured in the HMV-2000(Shimadzu) microhardness tester under 50 g loads for 15 s, and P was evaluated by percentage reductio of hardness after 24 h of alcohol storage. Data were subjected to t-Student test(alpha=0.05).QTH device showed lower P and higher KHN$ than LED (p<0.05), and no difference between the light-curing units was found for DC (p>0.05). The halogen-curing unit with higher irradiance promoted higher KHN and lower softening in alcohol than LED.